ADOPTION OF HALAL STANDARD IN MALAYSIAN FOOD INDUSTRY: A CASE OF SMALL AND MEDIUM ENTERPRISES - Azmi, F.R.; Abdullah, A.; Yahaya, S.H.; Woźniak, M.; Purnomo, M.R.A. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
The Halal industry has now expanded well beyond the food sector, further widening the economic potentials for Halal products. However, most of the SMEs are still reluctant to apply Halal standard (HS) and not seriously picture significance the power of Halal to gain competitive in the market. Thus, the aim of this study is to identify and analyse the adoption factors that motivate food manufacturers to adopt HS. A total 183 food manufactures certified by Halal take the survey of the study. The survey data were recorded using 5-points questionnaire. By conducting exploratory factor analysis, the findings yield that compatibility and perceived benefits are two factors grouped by technological factor. Halal integrity, Halal awareness, top management support, expected business benefits, understanding the practices and organisation readiness are six factors grouped by organisational factor. Lastly, Halal market demand, consumer pressure, competitive pressure and government support are four factors grouped by environmental factors. The paper includes implications for the halal food industry, whereby the adoption of HS will contribute to the business benefits to create a more competitive advantage to the industry.